HIV incidence, pregnancy, and implementation outcomes from the Sakh'umndeni safer conception project in South Africa: a prospective cohort study. Issue 7 (July 2019) - Schwartz, Sheree R; Bassett, Jean; Mutunga, Lillian; Yende, Nompumelelo; Mudavanhu, Mutsa; Phofa, Rebecca; Sanne, Ian; Van Rie, Annelies
Summary: Background: Safer conception strategies empower individuals trying to conceive to minimise HIV transmission risk to partners and potential children; however, effectiveness data are scarce. We aimed to assess adoption of safer conception methods and HIV and pregnancy outcomes from Sakh'umndeni, a novel safer conception service in South Africa. Methods: In this prospective cohort study, the Sakh'umndeni clinical cohort at Witkoppen Cinic in Johannesburg (South Africa) enrolled adults aged at least 18 years who were trying to conceive and in relationships with an HIV-positive partner. Couples who were pregnant at enrolment or had been previously diagnosed as infertile were excluded. Participants received safer conception care by a nurse, including antiretroviral therapy (ART) for HIV-positive partners, pre-exposure prophylaxis (PrEP) for HIV-negative partners, counselling around timed condomless sex, or syringes for self-insemination. Primary outcomes were pregnancy incidence and HIV transmission to partners and infants. We estimated time to first pregnancy using Kaplan-Meier curves; pregnancy and HIV incidence were estimated as events per person-years of risk. Findings: Between July 16, 2013, and April 5, 2017, 526 individuals (334 women and 192 men) from 334 partnerships enrolled. 162 (48%) of 334 couples were serodifferent, 149 (45%) were HIV-positive seroconcordant, and 23 (7%) were an HIV-positive woman and an unknown status male partner. At enrolment, 176 (61%) of 287 HIV-positive women and 60 (46%) of 131 HIV-positive men were virally suppressed (<50 copies per mL). Among the safer conception strategies, ART was initiated by 73 (91%) of 80 HIV-positive participants not on ART and PrEP was initiated by 28 (28%) of 101 HIV-negative participants. 2719 follow-up visits were completed, and 99 pregnancies were observed in 89 women. Pregnancy incidence was 41·2 per 100 person-years (95% CI 33·4–50·7); 25 (28%) of 89 pregnancies with a known outcome were miscarried or terminated because of risk to the mother. Pregnancy incidence was 79·0 per 100 person-years (95% CI 49·8–125·4) among HIV-negative women and 36·7 per 100 person-years (29·1–46·3) among HIV-positive women. At the time of pregnancy, viral suppression among women was high (68 [87%] of 78 women had viral loads of <50 copies per mL and 77 [99%] had viral loads of <1000 copies per mL). No horizontal or vertical HIV transmission events were observed. Interpretation: Safer conception strategies empowered couples to safely conceive. Pregnancy incidence among service users was high. Integration of safer conception counselling could promote HIV prevention and linkage to care. Funding: US Agency for International Development; UJMT Consortium/Fogarty International Center, US National Institutes of Health (NIH); and Johns Hopkins University Center for AIDS Research (NIH).